From canvas to stage: painting, theatre and revolution in Jacques-Louis David’s Brutus - Dessoldi, Flavia Giovana (Sala Preta, 2015)
The article discusses the French Revolution contribution to the field of arts, specifically to the field of performing arts: the importance of theater in this period and the legacy left after the influence of Revolution on the link between artistic languages analyzed from the relation between Jacques-Louis David’s Brutus, the play of same name staged in 1790 written by Voltaire, the new theatrical design that will be developed and the trajectory of Talma, an actor of Comédie Française that would later be established from his political position taken during the Revolution. It also analyzes the theater as a protest tool and as a mass mobilization.